2020
DOI: 10.3390/molecules25030762
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Flavonoids in Pain and Inflammation: Mechanisms of Action, Pre-Clinical and Clinical Data, and Pharmaceutical Development

Abstract: Pathological pain can be initiated after inflammation and/or peripheral nerve injury. It is a consequence of the pathological functioning of the nervous system rather than only a symptom. In fact, pain is a significant social, health, and economic burden worldwide. Flavonoids are plant derivative compounds easily found in several fruits and vegetables and consumed in the daily food intake. Flavonoids vary in terms of classes, and while structurally unique, they share a basic structure formed by three rings, kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
141
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(147 citation statements)
references
References 269 publications
(365 reference statements)
1
141
0
5
Order By: Relevance
“…During the last few years, flavonoids, including flavones, have attracted much interest because of their diverse bioactivities [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Recent studies have indicated the abilities of flavones in inhibiting many enzymes [ 25 , 26 , 27 , 28 , 29 ], especially AChE [ 30 ] and BACE-1 [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, flavonoids, including flavones, have attracted much interest because of their diverse bioactivities [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Recent studies have indicated the abilities of flavones in inhibiting many enzymes [ 25 , 26 , 27 , 28 , 29 ], especially AChE [ 30 ] and BACE-1 [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…This will repair liver cell damage. Phenolic compounds work as free radical scavengers, through the H + donor from hydroxyl groups (OH) in flavonoids against free radical compounds to form stable molecules (Ferraz et al, 2020;Mutee et al, 2010;Saryono et al, 2017). Previous studies showed that flavonoids in herb plants are useful for chelating free radicals by increasing endogenous antioxidant enzymes, reducing free radicals, and donating atoms.…”
Section: Resultsmentioning
confidence: 99%
“…five Bursera species in this study ( Table 5). The antioxidant activity of other Bursera species have been associated with lignans (Nieto-Yañez 2017, Marcotullio et al 2018) and phenols (Martinez-Elizalde et al 2018) Flavonoids such as hesperidin, apigenin, luteolin and quercetin, have anti-inflammatory and analgesic effects (Ferraz et al 2020). In a previous work, anti-inflammatory effects have been reported with an average effective dose (ED 50 ) of B. excelsa (0.26 ± 0.01 mg/ear), B. galeottiana (0.23 ± 0.02 mg/ear) and B. schlechtendalii (0.25 ± 0.02 mg/ear) from bark using chloroform extracts (Acevedo et al 2015).…”
Section: Discussionmentioning
confidence: 99%